Association between stroke occurrence and changes in atmospheric circulation - Jone Vencloviene; Ricardas Radisauskas; Daina Kranciukaite-Butylkiniene; Abdonas Tamosiunas; Vidmantas Vaiciulis; Daiva Rastenyte (BMC, 2021)
Abstract Background The impact of weather on morbidity from stroke has been analysed in previous studies. As the risk of stroke was mostly associated with changing weather, the changes in the daily stroke occurrence may be associated with changes in atmospheric circulation. The aim of our study was to detect and evaluate the association between daily numbers of ischaemic strokes (ISs) and haemorrhagic strokes (HSs) and the teleconnection pattern. Methods The study was performed in Kaunas, Lithuania, from 2000 to 2010. The daily numbers of ISs, subarachnoid haemorrhages (SAHs), and intracerebral haemorrhages (ICHs) were obtained from the Kaunas Stroke Register. We evaluated the association between these types of stroke and the teleconnection pattern by applying Poisson regression and adjusting for the linear trend, month, and other weather variables. Results During the study period, we analysed 4038 cases (2226 men and 1812 women) of stroke. Of these, 3245 (80.4%) cases were ISs, 533 (13.2%) cases were ICHs, and 260 (6.4%) cases were SAHs. An increased risk of SAH was associated with a change in mean daily atmospheric pressure over 3.9 hPa (RR = 1.49, 95% CI 1.14-1.96), and a stronger El Niño event had a protective effect against SAHs (RR = 0.34, 95% CI 0.16-0.69). The risk of HS was positively associated with East Atlantic/West Russia indices (RR = 1.13, 95% CI 1.04-1.23). The risk of IS was negatively associated with the Arctic Oscillation index on the same day and on the previous day (RR = 0.97, p < 0.033). During November-March, the risk of HS was associated with a positive North Atlantic Oscillation (NAO) (RR = 1.29, 95% CI 1.03-1.62), and the risk of IS was negatively associated with the NAO index (RR = 0.92, 95% CI 0.85-0.99). Conclusions The results of our study provide new evidence that the North Atlantic Oscillation, Arctic Oscillation, East Atlantic/West Russia, and El Niño-Southern Oscillation pattern may affect the risk of stroke. The impact of these teleconnections is not identical for various types of stroke. Emergency services should be aware that specific weather conditions are more likely to prompt calls for more severe strokes.